2017
DOI: 10.1177/0018578717721105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Rivaroxaban Patient Assistance Kit (R-PAK) for Patients Discharged With Rivaroxaban: A Randomized Controlled Trial

Abstract: The combination of poor health literacy and a complex dosing regimen/transition for rivaroxaban in venous thromboembolism (VTE) treatment may increase the likelihood of negative clinical outcomes secondary to nonadherence. The aim was to determine if a Rivaroxaban Patient Assistance Kit (R-PAK) given at hospital discharge increases proper dose transition and overall patient adherence. This prospective, randomized, controlled trial was conducted at an 859-bed academic medical center. Patients were randomized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…We identified only six studies 47,59,60,7072 describing interventions that specifically targeted older persons and two studies of interventions that specifically targeted those with limited health literacy. 28,31 The findings from one study 28 highlight the importance of assessing health literacy because of the positive correlation between health literacy and warfarin knowledge. This relationship between health literacy and knowledge was also highlighted in one study of patients with hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We identified only six studies 47,59,60,7072 describing interventions that specifically targeted older persons and two studies of interventions that specifically targeted those with limited health literacy. 28,31 The findings from one study 28 highlight the importance of assessing health literacy because of the positive correlation between health literacy and warfarin knowledge. This relationship between health literacy and knowledge was also highlighted in one study of patients with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Duplicates were removed, and the articles based on titles and abstracts were screened. For all articles, (including published conference abstracts), 31,38 the full-text version was retrieved and assessed according to the objectives of this review. The reference lists of the retrieved articles and review articles were examined manually to identify further relevant studies not identified using the search strategy.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations